Biomechanical report for the IAAF World Indoor Championships 2018 60m hurdles men - Walker, J.; Pollitt, L.; Paradisis, G.; Bezodis, I.; Bissas, A.; Merlino, S. (Leeds Becket University; Carnegie School of Sports, 2019)
The men`s 60 m hurdles took place on the evening of Sunday 4th March. As it was the final event of the IAAF World Indoor Championships in Birmingham, the pressure was on midlands-born Andrew Pozzi to provide Great Britain and N.I. with their first men`s medal of the championships. Pozzi went into the final as a potential favourite following his European Indoor Championships victory last year in Belgrade. However, other finalists such as Jarret Eaton and Aries Merritt (both United States) were showing good form throughout the season, whilst Pascal Martinot-Lagarde (France) and Milan Trajkovic (Cyprus) posted impressive times in the earlier rounds of these championships. At the start, Trajkovic was disqualified for a false start (IAAF Rule 162.8), meaning the final was to be contested between seven athletes. In the end, it was Pozzi who claimed the gold medallist with a season`s best performance of 7.46 s, just 0.01 s ahead of silver medallist Jarret Eaton (United States). France`s Aurel Manga claimed the bronze medal ahead of Aries Merritt.